0858 Sleep Disordered Breathing and Cardiopulmonary Indices in World Symposium of Pulmonary Hypertension Group 1 Pulmonary Hypertension. (12th April 2019) - Kaur, Sunjeet; Wang, Lu; Nawabit, Rawan; Highland, Kristin; Hill, Nicholas; Mehra, Reena; ,
Abstract: Introduction: Few studies have systematically investigated sleep disordered breathing(SDB) and rigorously collected cardiopulmonary measures in pulmonary hypertension(PH). We leveraged data from the NHLBI-funded multicenter Pulmonary Vascular Disease Phenomics(PVDOMICS) study focused on deep PH phenotyping to examine SDB and cardiopulmonary physiologic and structural measures in World Symposium of PH(WSPH) Group 1 PAH. Methods: The PVDOMICS study (NCT02980887) enrolls subjects ≥18 years of age referred for right heart catheterization (RHC) with mean pulmonary artery pressure≥ 25mmHg across seven clinical sites in the U.S. Sleep studies were included if conducted at home within 6 months of study enrollment using the NOX T3 (Carefusion®) or if available historically <1 year prior to enrollment. Linear regression was used to assess the association of sleep indices (apnea hypopnea index (AHI, ≥ 3% desaturation) and percentage total recording time <90%SaO2(TRT<90)) and cardiopulmonary measures (mean pulmonary artery pressure (mPAP), cardiac output, right ventricular wall measures and lung physiology) adjusted for supplemental oxygen and/or positive airway pressure usage (beta coefficients±95% confidence intervals). Results: 165 WPSH Group 1 participants comprise the sample to date: age 52.0± 14.1 years, 53% female, 78.2% Caucasian, body mass index(BMI) of 29.9± 7.7 kg/m 2 and 53.7% with AHI≥ 5. Each 5-unit increase in AHI was associated with a 0.80% reduction in FEV1% predicted (-0.16:-0.31, -0.02, p=0.002) and a nonsignificant 0.65% reduction of right ventricular ejection fraction (cardiac MRI) (-0.13: -0.28, 0.01, p=0.068). For every 5% increase in TRT<90, there was a 0.9mmHg increase in mPAP (0.18: 0.11, 0.26, p<0.001), a 1.15 mmHg increase in right ventricular systolic pressure (echocardiogram, ECHO) (0.23: 0.11, 0.35, p<0.001) and a 0.60% reduction in FEV1 (-0.12:-0.24, -0.01, p=0.036). Conclusion: While SDB severity defined by AHI was associated with reduced FEV1% predicted and a trend toward reduced RVEF (MRI), nocturnal hypoxia was associated with increased mPAP (RHC) and RVSP (ECHO) in WSPH Group 1 patients. These data show links between SDB severity and diminished pulmonary function and of nocturnal hypoxemia and severity of mPAP elevation; nocturnal hypoxemia therefore could represent a therapeutic target in Group 1 PAH. Support (If Any): U01HL125218/U01HL125205/U01HL125212/U01HL125208/U01HL125175/U01HL125215, U01HL125177/Pulmonary Hypertension Association